PENGAJARAN BAHASA DALAM PERSPEKTIF KUALITATIF: ANALISIS STRATEGI PEMBELAJARAN, INTERAKSI KELAS, DAN PENGUATAN LITERASI - Farida Nugrahani; Anwar Huda; Arif Wahyudi; Emi Listiya Utami; Sriatin; Paryati Paryati; Haniatul Ulfa; Anisa Shofiani (E-JURNAL AKSIOMA AL-ASAS, 2026)
This study aims to analyze language learning strategies, classroom interaction, and literacy development from a qualitative perspective. The study employed a descriptive qualitative approach involving teachers and students selected purposively. Data were collected through classroom observation, in-depth interviews, and documentation. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, and validated through source and technique triangulation. The findings reveal that teachers have implemented various strategies, such as communicative and text-based approaches, although not consistently. Classroom interaction is two-way, but student participation is uneven. Literacy development is carried out through reading and writing activities; however, it has not been optimally integrated into the learning process. The teacher’s role has shifted toward being a facilitator, although it remains dominant in certain situations. This study concludes that effective and meaningful language learning requires contextual strategies, inclusive interaction, and integrated literacy development. Therefore, reflective and innovative efforts are needed to create participatory and student-centered learning.